تمظهرات صورة اليهودي في الرواية العربية -التاريخ والاستشراف- رواية أنا وحاييم أنموذجا - أحمد, بن بغداد (جامعة الوادي - University of Eloued)
تتغيا هذه الدراسة، الغوص في التاريخ لاستقراء الأحداث التي دارت في الجزائر إبان الفترة الاستعمارية، من خلال رواية أنا وحاييم للحبيب السائح الذي حاول أن يصور الأحداث التي جمعت بين شخصيتين، عربية ويهودية، أزاحا عن طريقهما كل الخلفيات الأيديولوجية، واتفقا على بناء علاقة يغلب عليها طابع التعايش من أجل رص صفوف المجتمع والتأكيد على أن الاختلاف هو صورة من صور الرقي الاجتماعي، وقد استعنت بالمنهج الوصفي التحليلي للكشف عن تمظهرات شخصية حاييم في هذه الرواية، وإبراز التواشج القائم بين الشخصيتين، بعيدا عن كل المرجعيات التاريخية التي رسمت صراعا أزليا بين اليهود والعرب، ولم تترك أي مسافة لفكرة التسامح والتعايش. The events that occurd in Algeria during the colonial era through the novel of Me and Haim the Habib Essaih who tend to conceive the relation that gathered two personality from different nationalities Arabic nationality and a jewish one deleted from their way all the ideological back grounds and the doctrinal struggles and they agreed the build a relation dominated by the feature of coexistence for maintaing the building of society and ensuring on that deference is a picture of the social to pictures and in this study used the descriptive and analytic methodology reveal the appearances of Haim’s personality in their novel and demonstrate the harmony between the personality of the Arabic and the jewish far form the historial backgrounds that drew the eternal struggles conflict between Jews and Arabs and didn’t let any space for the ideas of tolerance and co-existence.
مقال
Keywords: الإيديولوجيا، التسامح، اليهودي، التاريخ، أنا وحاييم; ideology, tolerance, the Jew, History, me and Haim